PENGARUH WEBSITE QUALITY TERHADAP ONLINE PURCHASE INTENTION - Dea Aulya Putri Sundawa, - (2019)
This research aims to analyze the impact of website quality that consists of ease of use, information quality, enjoyment, security and service interaction quality on online purchase intention in HARRIS Hotel and Convention Ciumbuleuit Bandung. The type of this research is descriptive and verificative with the data analysis technique used is multiple regression techniques. The sample of this study are 96 individual guests who make a reservation through the hotel website. Simultaneously, the results show that the variable of website quality gives significant impact on online purchase intention at HARRIS Hotel and Convention Ciumbuleuit Bandung. The result of partial shows dimensions of website quality i.e. information quality has the highest impact, where HARRIS webstite Ciumbuleuit Hotel and Convention's website has high information quality. The results showed there was significant impact between website quality and online purchase intention.; Penelitian ini bertujuan untuk menganalisis pengaruh website quality yang terdiri dari ease of use, information quality, enjoyment, security dan service interaction quality terhadap online purchase intention di HARRIS Hotel and Convention Ciumbuleuit Bandung. Jenis penelitian yang dilakukan adalah deskriptif dan verifikatif serta teknik analisis data yang digunakan ialah teknik regresi berganda. Responden penelitian berjumlah 96 orang yaitu tamu individu yang melakukan reservasi melalui website hotel. Secara simultan, hasil penelitian menujukkan bahwa variabel website quality memiliki pengaruh signifikan terhadap variabel online purchase intention di HARRIS Hotel and Convention Ciumbuleuit Bandung. Secara parsial dimensi dari website yaitu information quality memiliki pengaruh tertinggi, dimana website HARRIS Hotel and Convention Ciumbuleuit memiliki kualitas dan ketersediaan informasi yang tinggi. Hasil penelitian menunjukkan terdapat pengaruh yang signifikan antara website quality terhadap online purchase intention.